Embedding digital and research-literacy support program into postgraduate studies curriculum: A proposed program for sub-Saharan African postgraduate schools. Issue 8 (27th October 2017) - Besseah, Bernard; Achiro, Daisy; Mhando, Joseph; Salau, Sadiat Adetoro
Abstract : Purpose: This viewpoint paper aims to propose a digital and research literacy support program for postgraduate schools in sub-Saharan Africa institutions. Design/methodology/approach: The paper reviewed literature on postgraduate students' skills and postgraduate information literacy programs and proposed one for postgraduate schools in sub-Saharan Africa institutions. Findings: Information literacy programs are not implemented at the postgraduate level in sub-Saharan Africa possibly because of lack of contents for these programs. Research limitations/implications: The course is only a proposed course that can be embedded into the postgraduate curriculum in sub-Saharan African universities. The effectiveness of the course has not been evaluated in this study. Originality/value: The proposed information literacy program focused on digital and research literacy, which is still relatively new in sub-Saharan Africa.